ANALYSIS OF CSR IMPLEMENTATION AS A COMPANY CONTRIBUTION IN ACHIEVING SUSTAINABLE DEVELOPMENT (CASE STUDY ON PT. OTSUKA INDONESIA) - Deviandini, Ellisa; Leniwati, Driana; Wahyuni, Endang Dwi; Juanda, Ahmad (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This study analyzes the implementation of CSR programs in a company engaged in the pharmaceutical industry. The purpose of this study is to find out whether PT Otsuka Indoenesia has implemented CSR programs in accordance with the Triple Bottom Line concept. In addition, this study also aims to analyze whether the implementation of CSR programs run by PT Otsuka Indonesia has fulfilled aspects of the Sustainable Development Goals. This research uses an interpretive paradigm with a qualitative descriptive approach. Data in this study were obtained through interviews and observations. The novelty of the study is related to the object of research and analysis of the company's contribution to the Sustainable Development Goals. The results show that the company has implemented CSR programs that are in accordance with the aspects and points contained in the Sustainable Development Goals. The Company runs CSR programs not only to fulfill its social responsibility but also to achieve the Sustainable Development Goals. However, companies need to develop their CSR programs into CSV programs, so that the programs run by the company not only provide benefits for program recipients, but also provide economic benefits to the company such as an increase in profits or an increase in sales at the company. Suggestions for future research are researchers to use research objects in other companies in order to find out whether companies in Indonesia have implemented CSR programs in accordance with the Sustainable Development Goals. So that Indonesia can achieve its Sustainable Development commitment in 2030.